RESPONSES OF PNP WOMEN’S DESK OFFICERS’ TO VIOLENCE AGAINST WOMEN - Ruby Ann L., Espineli; Marissa C., Lontoc; Myleen P., Legaspi (European Scientific Journal, ESJ, 2015)
The study mainly assessed the responses of WCPD officers on cases of violence against women. Further, the problems encountered during their responses were also highlighted.Survey questionnaire and interview were used to gather data from twenty three WCPD officers and five abused women from each city and municipality in Cavite. Findings revealed that RA 9262 (Anti-Violence against Women and Children) is the most common violation committed against women.Also, majority of the perception of the WCPD officers and abused women on the responses of the WCPD officers on cases of VAW are similar. During initial response, in terms of receiving complaint, officers basically ask the full name and address of the caller/abused women to establish their identity. In contrast, they cannot respond at the scene within 5 minutes due to unavailability of marked vehicle. In terms of after call/complaint, WCPD officers immediately call the attention of their co-officers to assist them. However, they do not often coordinate with the involved barangay. In the arrival at the scene, in case the abused woman was injured, officers advise her to undergo medicolegal examination, likewise, inquire on the nature of dispute for comprehensive investigation. However, they seldom execute arrest, because sometimes, perpetrator already escaped or the dispute is already settled.Further, in the conduct of interview, asking question at a time and free narrative were the strategies of officers to give abused women the time to answer each question. In contrast, WCPD officers seldom use gadgets that would facilitate the interview because of its unavailability.On the other hand, in filing the complaint, it indicated contradicting perceptions. For WCPD officers, they acquire copies of marriage contract and birth certificate since most of the cases involved marital violence while for abused women, they highly perceived that medical records is the most requested document.The problems encountered by WCPD officers in responding to VAW cases are: uncooperativeness of the caller/complainant, unavailability of facilities and WCPD officer inadequacy of knowledge on laws result to slow police service.